2004
DOI: 10.1002/mrd.20038
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effect of gamma‐aminobutyric acid on bovine spermatozoa capacitation

Abstract: Sperm capacitation is defined as the maturational changes that render a sperm competent for fertilization and occurs in the female reproductive tract. Identification of the factor/s that regulate sperm capacitation would allow the understanding of these phenomena. Among these factors, gamma-aminobutyric acid (GABA) has recently become as a putative modulator of sperm function. The aim of this study was to explore the presence of a GABAergic regulation of bovine sperm capacitation as well as the possible intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…GABA A-receptor has been identified in human spermatozoa. In a recent study, the in vitro effect of GABA was studied on bovine spermatozoa capacitation [120]. It was observed that addition of GABA to the incubation medium results in a concentration-dependent increase in the percentage of capacitated spermatozoa.…”
Section: Protein Tyrosine Phosphorylation In Spermatozoamentioning
confidence: 99%
“…GABA A-receptor has been identified in human spermatozoa. In a recent study, the in vitro effect of GABA was studied on bovine spermatozoa capacitation [120]. It was observed that addition of GABA to the incubation medium results in a concentration-dependent increase in the percentage of capacitated spermatozoa.…”
Section: Protein Tyrosine Phosphorylation In Spermatozoamentioning
confidence: 99%
“…In addition, high concentrations of GABA exist in seminal plasma [3,4]. This evidence suggests that GABA may exert a regulatory role in mammalian sperm function [5].…”
Section: Introductionmentioning
confidence: 99%
“…In early neurogenesis, GABA A stimulation was shown to depolarize, rather than to hyperpolarize cells, and this led to elevated Ca 2+ levels via opening of voltage-gated calcium channels [56,57,58,59]. Furthermore the second messenger cAMP has been implicated in neural and non-neural GABA A receptor signal transduction [29,30,31,32]. Importantly, in some cases the depolarizing GABA A currents have been reported to be very small (1–4 pA) [23], a fact that may be related to only few receptors on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…The way of action of the GABA A receptor in immature neurons, contrary to mature neurons, is associated with depolarization of the cell membrane [14, 26, 27]. Despite the fact that there are many reports of non-synaptical GABA effects and actions, little is known about the subsequent intracellular pathways, but increased Ca 2+ levels and altering cAMP levels are two documented possibilities [24,28,29,30,31,32]. …”
Section: Introductionmentioning
confidence: 99%